Pemalsuan Bukti C1 Rekapan Pada Proses Pemilihan Legislatif - Marcellino Lessil; Elsa Rina Maya Toule; Denny Latumaerissa (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The crime of forgery of letters committed by prospective members of the legislature, legally the crime of forgery that occurs is a form of general election crime.Purposes of the Research: This study aims to determine, examine, and analyze the application of the law and the reasons for termination in the case of falsification of evidence C-1 recap in the legislative election process. Methods of the Research: The research method in this writing uses a normative juridical research type. The research approach used is a statutory approach and a conceptual approach. The procedure for collecting legal materials uses library research, as well as legal material analysis techniques in this study using qualitative analysis techniques.Results of the Research: The research method in this paper uses a normative juridical research type. The research approach used is a statutory approach and a case approach. The procedure for collecting legal materials uses library research, as well as legal materials analysis techniques in this study using qualitative analysis techniques